Effects of Slow-Stroke Back Massage on Symptom Cluster in Adult Patients With Acute Leukemia: Supportive Care in Cancer Nursing. Issue 1 (January 2017) - Miladinia, Mojtaba; Baraz, Shahram; Shariati, Abdolali; Malehi, Amal Saki
Abstract : Background: Patients with acute leukemia usually experience pain, fatigue, and sleep disorders, which affect their quality of life. Massage therapy, as a nondrug approach, can be useful in controlling such problems. However, very few studies have been conducted on the effects of massage therapy on the complications of leukemia. Objective: The aim of this study was to examine the effects of slow-stroke back massage (SSBM) on the symptom cluster in acute leukemia adult patients undergoing chemotherapy. Methods: In this randomized controlled trial, 60 patients with acute leukemia were allocated randomly to either the intervention or control group. The intervention group received SSBM 3 times a week (every other day for 10 minutes) for 4 weeks. The pain, fatigue, and sleep disorder intensities were measured using the numeric rating scale. The sleep quality was measured using the Pittsburgh Sleep Quality Index. Statistical tests of χ 2, t test, and the repeated-measure analysis of variance were used for data analysis. Results: Results showed that the SSBM intervention significantly reduced the progressive sleep disorder, pain, fatigue, and improved sleep quality over time. Conclusions: Slow-stroke back massage, as a simple, noninvasive, and cost-effective approach, along with routine nursing care, can be used to improve the symptom cluster of pain, fatigue, and sleep disorders in leukemia patients. Implications for Practice: Oncology nurses can increase their knowledge regarding this symptom cluster and work to diminish the cluster components by using SSBM in adult leukemia patients.